Duality Linguistic and Its Impact on Arabic Language - Almnaizl, Tamam Hamad (Arab Journal for Sciences and Research Publishing, 2020)
The research dealt with six axes. In the first topic, the study dealt with the definition of the language in general at the linguists of the Arabs and the West, and concluded that the language is a means of communication through which all people express their purposes.In the second axis, the research dealt with the concept of linguistic and bilateral duality in many researchers, and concluded that duplication and dualism is one thing that occurs between one language, such as the phonetic and the colloquial, or between two different languages.In the third axis, the research dealt with the emergence of duplication in Arabic, and that it existed since the pre- Islamic era, but it was not as serious as it is now. In the fourth axis, he talked about the manifestations of duplication and its causes, and that there are two manifestations of duplication: the first is the writing, the duality took two forms of circulation: drawing and writing for the Pharaonic, The second appearance is the language of Almchafha, which is the language of conversations, and common in public places, and were not written, and talked about the reasons that led to the existence of this phenomenon. In the fifth axis, the study dealt with the problem of duplication and the fact that it is a problem of serious problems that affect the classical language, fear of the colloquial place and the disappearance of Mandarin, and other things that confirm the seriousness and prove to be a problem. In the last axis, the research dealt with the proposed solutions and possible solutions to the problem of duplication, there were three solutions: the first recognition of the reality of language and the delivery of duplication, and the adoption of the traditional only, or the vernacular only to unite on one, and the third approximation between them.
Keywords: Linguistic duality; Arabic language; Classical Arabic; Colloquial Arabic